(untitled) (International journal of artificial intelligence, 2024)
In this research I will explain how hard to make decision to the entrepreneurs for their business success and what kind of consequences are waiting them after their decision. Moreover, there will be analysis of their decision for the growth of their business or negative impacts. There will be several famous companies and different industries that increased or decreased of their value in the market in order to making their owners or CEO`s decision. In short, usually it is hard to make decision because it is so risky even it gives more profit while it gives loses.